Accuracy of near-infrared interactance instruments and population-specific equations for estimating body composition in young wrestlers - Housh, T. J.; Johnson, G. O.; Housh, D. J.; Cramer, J. T.; Eckerson, J. M.; Stout, J. R.; Bull, A. J.; Rana, S. R. (The Journal of Strength and Conditioning Research, 2004)
The purpose of this investigation was to determine the accuracy of near-infrared interactance (NIR) instruments and population-specific NIR equations for estimating percent body fat (% fat) in young wrestlers. Forty-four white male youth wrestlers (mean age ± SD = 11.0 ± 2.1 years) volunteered for this study. Thirteen NIR % fat estimates were cross-validated against the criterion % fat from underwater weighing. The results of this study indicated that the total error (TE) values associated with the NIR instrument generated % fat estimates as well as % fat estimates from population-specific NIR equations developed for high school wrestlers or adult men were too large (TE = 5.7-27.3% fat) to be used with young wrestlers. Based on the present findings, it is recommended that new NIR equations be developed and validated specifically for use in young male athletes.